PENGARUH BELANJA MODAL, BELAJA NON MODAL, PENANAMAN MODAL ASING, DAN PENANAMAN MODAL DALAM NEGERI TERHADAP KEMISKINAN KALIMANTAN SELATAN - Hanifah Safitri; Muhammad Saleh (PPJP Universitas Lambung Mangkurat, 2020)
This study was conducted to determine the effect of capital expenditure, non-capital expenditure, Foreign Investment (PMA) and Domestic Investment (PMDN) on poverty rate in South Kalimantan Province.This research is a quantitative research. The data used in this study are secondary data from South Kalimantan Province in 2008-2017. The analysis technique in this study uses multiple linear regression analysis with time series data.The results of this study are based on a regression analysis that capital expenditure has a negative and significant effect on poverty rate in South Kalimantan, non-capital spending has a positive and not significant effect on poverty rate in South Kalimantan, PMA has a negative and significant effect on poverty rate in South Kalimantan, and PMDN has a negative and notsignificant effect to the poverty rate of South Kalimantan.Keywords: Poverty, Capital Expenditure, Non-Capital Expenditure, Foreign Investment, Domestic Investment.